Role of downwelling/upwelling in formation/destruction of hypoxia in the bottom waters of the Amur Bay (Japan Sea) - Petr P. Tishchenko; Pavel Ya. Tishchenko; Vyacheslav B. Lobanov; Alexander F. Sergeev; Pavel Yu. Semkin (Известия ТИНРО, 2015)
Downwelling/upwelling influence on hypoxia at the bottom of the Amur Bay is determined on the data of oceanographic surveys conducted aboard RV Impulse in August 2012 and RV Malachite in August 2013 coupled with the data of monitoring oceanographic station in the bay. The hypoxia develops in the period of downwelling circulation driven by southern and southeastern winds and relaxes in conditions of upwelling induced by northern and northwestern winds.